Implementasi Aspek Promotif Upaya Kesehatan Jiwa di Malang - Zuhrotun Ulya (Center for Health Policy and Management, 2018)
Mental disorders require holistic management that involves families and communities to make mental health communities. Education about mental disorders and emergency psychiatry is expected to be able to direct and foster participant activities to better recognize the importance of mental health. This research was conducted through the education as a promotive aspect of mental health involving 45 participants from various component of community which were evaluated for implementation through educational processes and results. The implementation of education on mental disorders as a promotive aspect of mental health make mindset and attitudes of society that mental disorders can be treated appropriately and as an alternative of empowering mental health communities in Malang.